Financial accounting and reporting : standards and applications : PFRSs and PASs-based : volume 1 - Cabrera, Ma. Elenita Balatbat; Ocampo, Reynaldo Royo (Recto, Manila : GIC Enterprises & Co. Inc., 2013)
This book's mission is to address the need for a textbook that presents critical concepts and principles based on the accounting standards issued by the International Accounting Standards Board (IASB) and Financial Reporting Standards Council (FRSC) in a clear, concise way that is most helpful to learning an to enhancing the user's interests.
I. Financial accounting and reporting fundamentals -- II. Financial Assets: Accounting and reporting -- III. Non-financial assets: accounting and reporting -- References.
Includes bibliographical references.
Keywords: ACCOUNTING